Relationship Between Level of Knowledge with Behavior Using Personal Protective Equipment among Laboratory Workers at Al-Ihsan Hospital, Bandung, West Java - Sekarningtyas Rahardianti Putri; Endang Dwiyanti (Journal of Health Promotion and Behavior, 2023)
Background: Personal protective equipment (PPE) is mandatory equipment for workers to use while working in accordance with the hazards and risks that are being faced. This behavior of using PPE itself aims to isolate the workers’ bodies from hazards and risks of occupational accidents. Based on the results of observations, laboratory workers of Al-Ihsan Hospital Bandung still often ignored the use of PPE which may inflict the risk of the occurrence of occupational accidents.  This study aims to analyze the relationship between the level of knowledge and the behavior of using PPE among laboratory workers of Al-Ihsan Hospital Bandung, West Java. Subjects and Method: It was a quantitative study with a cross-sectional study design conducted at Al-Ihsan Regional General Hospital Bandung from June to September 2022. The sample used was 43 laboratory workers. The dependent variable was the behavior of using personal protective equipment (PPE). The independent variable was the level of knowledge. Data collection was carried out using an online questionnaire. The data were analyzed using the Chi-Square test. Results: The level of knowledge relates to the use of PPE. Well-informed workers increased the behavior of using PPE by 60.0 times compared to workers with a low level of knowledge and it was statistically significant (OR= 60.0; 95% CI= 8.98 to 400.8; p<0.001). Conclusion: The level of knowledge is significantly related to the behavior of using PPE. Keywords: behavior of using ppe, level of knowledge, and laboratory workers. Correspondence: Endang Dwiyanti. Study Program of Public Health, Universitas Airlangga. Jl. Kebonsari Elvenka II Cluster Graha Mas 36-37 Surabaya, East Java. Email: endang.dwiasfar@fkm.unair.ac.id. Mobile: +6282132330900